2006
DOI: 10.1029/2005gl025074
|View full text |Cite
|
Sign up to set email alerts
|

Satellite data reveal the 3‐D moisture structure of Tropical Intraseasonal Oscillation and its coupling with underlying ocean

Abstract: [1] The water-vapor profiles obtained from the Atmospheric Infrared Sounder (AIRS) on Satellite Aqua are used to document the 3-D moisture structure of the boreal-summer Tropical Intraseasonal Oscillation (TISO) over the Indo-western Pacific region. With the support of several other Satellite data sets, the interactions between the TISO and underlying ocean are also investigated. The AIRS data reveal much larger tropospheric moisture perturbations than those depicted in previous reanalysis and analysis data se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
89
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(105 citation statements)
references
References 22 publications
13
89
2
Order By: Relevance
“…For example, the near-surface cooling and drying may indicate the influence of enhanced or suppressed convective downdrafts on the boundary layer (Fu et al 2006). It is also possible that the intraseasonal sea surface temperature (SST) anomalies may contribute to the low-level moist thermodynamic preconditioning by enhancing turbulent surface fluxes or low-level meridional convergence associated with the frictional wave-CISK (Shinoda et al 1998;Waliser et al 1999;Fu et al 2006). To fully understand this issue, detailed energy and moisture budget studies based on high-quality data of boundary layer wind, SST, and surface heat fluxes are needed.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For example, the near-surface cooling and drying may indicate the influence of enhanced or suppressed convective downdrafts on the boundary layer (Fu et al 2006). It is also possible that the intraseasonal sea surface temperature (SST) anomalies may contribute to the low-level moist thermodynamic preconditioning by enhancing turbulent surface fluxes or low-level meridional convergence associated with the frictional wave-CISK (Shinoda et al 1998;Waliser et al 1999;Fu et al 2006). To fully understand this issue, detailed energy and moisture budget studies based on high-quality data of boundary layer wind, SST, and surface heat fluxes are needed.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The advection of moisture by the mean flow and moisture advection resulting from mean meridional intraseasonal winds in the boundary layer are essential factors favoring northward propagation (Jiang et al 2004). The third factor that may enhance northward propagation is the intraseasonal variation of SST, which is shown to guide convection in the northward-propagating BSISO Fu et al 2003). The above-mentioned theories demand the following on intraseasonal time scales:…”
Section: A Theorymentioning
confidence: 99%
“…Recent modeling and observation studies (e.g., Fu et al 2003;Sengupta et al 2001) emphasize the crucial role of air-sea interactions in defining the observed phase structure of BSISO. Fu et al (2003) suggests that warm (cold) SSTs lead the northward-propagating wet (dry) phase of convection in the north Indian Ocean by about 10 days.…”
Section: Air-sea Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact reason is not clear, it is generally believed that inadequate representation and description of moisture processes and the associated scale interactions are likely the major culprit (Fu et al 2006;Sooraj and Seo 2013;Demott et al 2014). Some recent studies have suggested that interactions between different cloud regimes, circulation, and diabatic heating in the boundary layer may play a critical role for the evolution of the BSISO (Chattopadhyay et al 2009;Jiang et al 2011;Abhik et al 2013).…”
Section: Introductionmentioning
confidence: 99%